2018
DOI: 10.1039/c7dt02616a
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-mediated selective delivery of a cytotoxic cationic NHC-Au(i) complex to cancer cells

Abstract: A novel cationic NHC-Au(i) complex was synthesized and studied for its antitumor activity. For all the cell lines tested, cationic NHC-Au(i) complex 2 shows much higher cytotoxicity than its neutral analogue 1. To achieve selective cancer cell targeting, complex 2 was covalently conjugated to aptamer AS1411, a DNA aptamer with strong binding affinity for nucleolin. The successful conjugation was confirmed by HPLC, gel electrophoresis, fluorescence spectroscopy and UV-Vis absorption. Conjugate AS1411-2 was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…40 Moreover, enrichment and separation by magnetic particles and fluorescence detection by gold nanoclusters (AuNCs) are powerful tools for their evaluation because of their controllability and high sensitivity. 41,42 In one study, Cheng et al indicated a new method for the detection of S. aureus in which recognition molecules, such as an aptamer, and antibiotic were combined together. In this study, S. aureus was quantified via the use of aptamer-coated magnetic beads (Apt-MB) and Vancomycin (Van)-functionalized fluorescent nanoclusters (AuNCs@Van, with 2.0±0.6 nm) in a mixture of other non-targeted bacteria and was also detected in authentic samples including milk and human serum.…”
Section: Introductionmentioning
confidence: 99%
“…40 Moreover, enrichment and separation by magnetic particles and fluorescence detection by gold nanoclusters (AuNCs) are powerful tools for their evaluation because of their controllability and high sensitivity. 41,42 In one study, Cheng et al indicated a new method for the detection of S. aureus in which recognition molecules, such as an aptamer, and antibiotic were combined together. In this study, S. aureus was quantified via the use of aptamer-coated magnetic beads (Apt-MB) and Vancomycin (Van)-functionalized fluorescent nanoclusters (AuNCs@Van, with 2.0±0.6 nm) in a mixture of other non-targeted bacteria and was also detected in authentic samples including milk and human serum.…”
Section: Introductionmentioning
confidence: 99%
“…All the cell lines showed resistance to neutral complex 284 (IC 50 value is >100 μM) except CCRF‐CEM cell line which showed IC 50 value 31.3±2.11 μM. The authors concluded that higher cytotoxicity is due to the presence of a delocalized lipophilic cation that can easily penetrate through the hydrophobic cell membrane [164] …”
Section: Medicinal Applicationsmentioning
confidence: 97%
“…Additionally, AS1411 modified with FITC (fluorescein isothiocyanate) on its 3′ end, an amine group on its 5′ and six extra T bases to prevent fluorescent (5′-TTT TTT GGT GGT GGT GGT TGT GGT GGT GGT GG TTT TTT-FITC-3′) was used to react with N-heterocyclic carbene (NHC)-Au(I) [ 38 ]. The aptamer-NHC-Au(I) conjugate exhibited higher recognition and binding to the target cancer cells (MDA-MB-231, HeLa and DU145 cell lines) as demonstrated by flow cytometry and confocal microscopy [ 38 ].…”
Section: G-quadruplex Structures As Drug Delivery Systemsmentioning
confidence: 99%
“…Additionally, AS1411 modified with FITC (fluorescein isothiocyanate) on its 3′ end, an amine group on its 5′ and six extra T bases to prevent fluorescent (5′-TTT TTT GGT GGT GGT GGT TGT GGT GGT GGT GG TTT TTT-FITC-3′) was used to react with N-heterocyclic carbene (NHC)-Au(I) [ 38 ]. The aptamer-NHC-Au(I) conjugate exhibited higher recognition and binding to the target cancer cells (MDA-MB-231, HeLa and DU145 cell lines) as demonstrated by flow cytometry and confocal microscopy [ 38 ]. Moreover, by MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay, enhanced cytotoxicity was observed when AS1411- NHC-Au(I) conjugate was applied to cancer cell lines and did not significantly reduce proliferation in two healthy normal cell lines (HEK293 and HU1545v) [ 38 ].…”
Section: G-quadruplex Structures As Drug Delivery Systemsmentioning
confidence: 99%
See 1 more Smart Citation